2022
DOI: 10.1002/admt.202101281
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Interconnected Cu‐Ni Nanoalloys Decorated Carbon Nanotube‐Poly(vinylidene fluoride) Piezoelectric Nanogenerator

Abstract: Herein, high‐performance flexible and stable Cu‐Ni nanoalloy decorated carbon nanotube (CNT) reinforced poly(vinylidene fluoride) (PVDF) based piezoelectric nanogenerator is presented for the first time with very high current and power density. The formation of crystalline β‐phase is confirmed using FT‐IR and Raman spectra analysis. HR‐TEM study reveals the formation of Cu‐Ni nanoalloys with well‐defined interconnected structure with CNT. The Cu‐Ni nanoalloy decorated CNT‐PVDF nanogenerator device exhibits a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…The reason can be attributed to the increase in the number of dipoles of the PVDF matrix and the interface polarization enhanced by the addition of TiO 2 NRs. 54 As shown in Figure S7b, all nanofiber films exhibited low dielectric loss values in the measured frequency range, which is beneficial to improve the breakdown strength of the composite nanofiber membrane. Figure S7c illustrates the AC conductivity as a function of frequency, and the results show that ARTP has a larger value.…”
Section: Characterization Of Tio 2 Nrs and Tp Composite Nanofibrous M...mentioning
confidence: 79%
“…The reason can be attributed to the increase in the number of dipoles of the PVDF matrix and the interface polarization enhanced by the addition of TiO 2 NRs. 54 As shown in Figure S7b, all nanofiber films exhibited low dielectric loss values in the measured frequency range, which is beneficial to improve the breakdown strength of the composite nanofiber membrane. Figure S7c illustrates the AC conductivity as a function of frequency, and the results show that ARTP has a larger value.…”
Section: Characterization Of Tio 2 Nrs and Tp Composite Nanofibrous M...mentioning
confidence: 79%
“…Besides, the performance of PVDF nanofibers can be further enhanced by adding nanofillers. [7,15,22] For instance, in the cowpea structure proposed by Deng et al, [23] the ZnO nanospheres were well wrapped in PVDF nanofibers, and results showed that with 5% ZnO, the 𝛽-phase content, as well as the output voltage, increased (by more than 5 times) compared to the pristine PVDF nanofibers. Moreover, carbon-based materials are commonly used to increase the piezoelectricity of PVDFbased nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Piezoelectric nanogenerators have gained significant attention in recent years as a viable method of converting mechanical energy to electrical energy. 12 It is also possible to combine the piezoelectric nanogenerator with capacitors or batteries for the conversion and storage of mechanical energy through chemical reactions simultaneously. When piezoelectric materials are subjected to sufficient force, an external electric field is created, which causes a stirring of the positive and negative charge centers.…”
Section: Introductionmentioning
confidence: 99%